LIVRO DISCUTE A PRESENÇA DE WEBER NAS FILOSOFIAS DE HABERMAS, ARENDT E MACINTYRE - Aires de Carvalho, Helder Buenos (Pensando - Revista de Filosofia, 2015)
N, Keith. Under Weber’s Shadow: Modernity, Subjectivity and Politics in Habermas, Arendt and Macintyre. Ashgate Publishing Co., 2012. Keith Breen é Lecturer de Political Theory na School of Politics, International Studies and Philosophy, Queen’s University Belfast, Northern Ireland. "Under Weber’s Shadow" presents an extended critical evaluation of the social and political thought of Jurgen Habermas, Hannah Arendt and Alasdair MacIntyre. Although hailing from very different philosophical traditions, these theorists all take as their starting-point Max Weber’s seminal diagnosis of late modernity, the view that the world-historic processes of rationalization and disenchantment are paradoxical in promising freedom yet threatening servitude under the ’iron cage’ of instrumental reason. However, each rejects his pessimistic understanding of the grounds and possibilities of political life, accusing him of complicity in the very realities he sought to resist. Seeking to move beyond Weber’s monological view of the self, his subjectivism and his identification of the political with domination, they offer alternative, intersubjective conceptions of the subject, ethics and politics that allow for positive future possibilities. But this incontrovertible gain, it is argued, comes at the cost of depoliticizing key arenas of human endeavour and of neglecting the reality of struggle and contestation. Engaging with important current debates and literature, Keith Breen provides a rigorous analysis of the work of Habermas, Arendt, MacIntyre and Weber and a highly accessible and original intervention within contemporary social and political thought. "Under Weber’s Shadow" will therefore be of interest to students and researchers alike within the areas of social and political theory, as well as those within the disciplines of ethics, sociology and philosophy.